Development of an adjustable measuring system for electrical consumptions in production - Spreng, Simon; Kohl, Johannes; Franke, Jörg (Applied Mechanics and Materials, 2014)
The establishment of green products and a sustainable production increasingly affects corporate competitiveness, as an efficient production does not only affect the energy costs, but also improves the company image. As the importance of renewable energy sources increases, mainly providing unsteady energy levels, load management of manufacturing and assembly lines fades into spotlight. For this purpose, proper measuring equipment is required, being able to log and evaluate varying energy loads.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electrical consumption; Energy management; Measuring system; OPC UA